A comparative analysis of interface quality of mobile access to the services of selected banks - Kurzyna, Marcin; Matysiak, Damian; Miłosz, Marek (Journal of Computer Sciences Institute, 2017)
This paper is focused on comparison of interface quality of mobile access to the services of selected banks. Main factors, which were used in the comprising process are: safety, availability on the mobile platforms, time and simplicity of task performing, intelligibility, design, comfort, number of functions. Research was made using 4 methods: surveys, corridor tests, expert tests and eyetracking. As a result T-Mobile Banking Services won in three categories: intelligibility, design and simplicity while mBank is better in responsiveness, availability and has more functions to offer